Meet me under the mistletoe - Bayliss, Jenny (G. P. Putnam's Sons, 2022)
"A romantic small-town holiday read about a bookshop owner and her unexpected reunion with a childhood enemy, told with Bayliss's trademark humor, warmth, and Christmas spirit"--